The female athlete Triad: Too fit to quit or too thin to win? - Otis, C. L. (2000)
The Female Athlete Triad consists of the interrelated problems of disordered eating, amenorrhoea and osteoporosis. These disorders lead to decreased athletic performance and medical and psychological problems, through inadequate nutrition, loss of lean muscle mass, dehydration, decreased bone strength, increased risk of injuries and heart problems. The Triad may be an indicator of overtraining. Coaches are in a critical position to prevent, recognise, and refer women with one or all aspects of the Triad. It is shown that exercise does not cause the triad but there are pressures on athletic women. The result are eating disorders, stress fractures and osteoporosis.